Answer:
y =-14
Step-by-step explanation:
Inverse variation is of the form
xy = k where k is a constant
(-7)(-8) = k
56 = k
The equation is
xy = 56
Let x = -4
(-4)y = 56
y = 56/-4
y =-14
X(x+3)-7(x+3)
x2+3x-7x-21
x^2-4x-21
Sum of linear pair of angles = 180°
so
<EFG + <GFH = 180°
2n + 21 + 4n + 15 = 180°
6n + 36 = 180°
6n = 144
n = 24
<EFG = 2(24) + 21 = 69°
<GFH = 4n + 15 = 4(24) + 15 = 111°
Answer:
n=3
m=2
Step-by-step explanation:
This done by factorizing thier powers.
Answer:
all work is shown and pictured